Utilization of Intravenous (IV) Curcumin, Genistein, and Trastuzumab to Reduce HER2 receptors in Breast Cancer Patients - Shreya Bhandari; Hasmitha Kamineni (International Journal for Research in Applied Sciences and Biotechnology, 2021)
In recent decades, due to the increased growth, spread, and onset of cancer, interest has arisen in studying the methods that could be used to combat it. Breast cancer is the most prevalent form of cancer in the world. Due to the growing pervasiveness of this issue, a larger body of research is forming in the area of breast cancer with the intent to contain the spread of the potentially ravaging disease or diagnose it earlier. This research is intended to propose an alternative, possibly more efficient method to inhibit the chances of metastasis and continued prevalence of breast cancer in a patient. The related work discusses similar research being done and builds on it to incorporate the novel method being proposed while explaining the components of the proposed treatment in question. The proposed method aims to deplete HER2 protein receptors in breast cancer patients through the intravenous (IV) administration of the tyrosine kinase inhibitors (TKIs) curcumin and genistein, as well as trastuzumab, which is more commonly known under the brand name Herceptin. Depleting HER2 protein receptors can potentially cause the severity of HER2-positive breast cancer to decrease substantially, as well as reduce the probability of metastasis and recurrence, the rate of which is considerably higher in HER2-positive cases when compared to that of HER2-negative cases. The future work deals with alternate methods that could be explored with a similar intent as this research study and describes the potential implications of the study.